The Effect of Group Discussion Learning on Improving Students' Critical Thinking Skills in Essay Writing - Musoffa, Laylatul; Anggraeni, Astri Widyaruli; Citraningrum, Dina Merdeka (Journal of Educational Sciences, 2025)
This study aims to evaluate the impact of the group discussion learning approach on improving students' critical thinking skills in writing essays for Indonesian language subjects at SMP Negeri 1 Tempurejo. This study uses a quantitative approach with a pretest-posttest design with a non-equivalent control group. The participants consisted of two classes: IX B as the control group and IX D as the experimental group, each containing 20 students. Data were collected using essay writing assessments and direct observation to evaluate student engagement during classroom learning, after which they were evaluated using a paired sample t-test. The results showed an increase in the average score of the experimental class from 77.5 to 91.3 (an increase of 13.8 points), while the control class increased from 56.8 to 66.9 (an increase of 10.1 points), indicating a significant difference between the two classes. The experimental class experienced a percentage increase of 17.81%, indicating a relative effectiveness that was 36.63% superior to the standard learning method. As a result, the group discussion method significantly improved students' critical thinking skills in essay writing.